(untitled) (International journal of artificial intelligence, 2025)
This article explores the significance of Boburnoma in shaping students' moral and ethical values. As an autobiographical and historical work by Zahiriddin Muhammad Babur, Boburnoma provides valuable insights into leadership, patriotism, cultural heritage, and personal integrity. The study highlights how the text serves as an educational resource, fostering a sense of identity, resilience, and intellectual growth among students. By integrating Boburnoma into the educational curriculum, educators can enhance students' appreciation for history, literature, and ethical decision-making. The article also discusses methods for effectively utilizing Boburnoma in student character development.